Therapeutic Effect of Comedy Films on Decreasing of Depression in the Schizophrenic Patients - Farbod Fadaei; Maryam Pourreza; Kianoosh Hashemian (University of Social Welfare and Rehabilitation Sciences, 2004)
Objective: This research is an evaluation of the theraputic efficacy of comedy films in improving the mood of the long - stay schizophrenic inpatients. Materials & Methods: 50 schizophrenic patients in 2 rehabilitation wards of Razi Psychiatric - Center were selected on the basis of available sampling. They were divided into 2 groups (Experimental and Control), each group consisted of 25 patients. Before any therapeutic procedure, the magnitudes of their depression were measured by Beck Depressive Inventory. Afterwards, the experimental group was exposed to silent comedies of Charles Chaplin and Mr. Bean (Roan Atkinson) for 30 minutes every other day for two weeks. Meanwhile, the control group were shown a documentary film about the formation of planet Earth. At the end of the second week, the magnitude of depression of all cases were again measured by B.D.I. Furthermore, in order to investigate the statistical significance of differences between depression magnitude among both groups before and after the experiment, Mann Withney - U test, was utilized. Also for defining and explaining the data and drawing the scales, SPSS and Excel softwares were employed as well. Results: According to the findings of this research, the difference between depression magnitude in both groups before and after the exposure to comedy films was significant at P=0.05. Conclusion:  This result shows that comedy films can improve the depressed mood in the long-stay schizophrenic people.